Perception and adaptation of pastoralists to climate variability and change in Morocco's arid rangelands. Issue 11 (November 2021) - Snaibi, Wadii; Mezrhab, Abdelhamid; Sy, Oumar; Morton, John F.
Abstract: Since the late 1970s, extensive livestock production in the high plateaus of Eastern Morocco, particularly of small ruminants, has been seriously threatened by climate change (CC). Negative impacts include reduction in rangeland forage production and water availability, increased poverty and inequality, and increased degradation of rangelands. Different categories of pastoralists have adopted different combinations of adaptation strategies, but the factors influencing adoption have not to date been investigated. This paper aims to identify the perceptions of pastoralists on CC, to analyze the adaptive responses of different wealth categories, and to determine the factors affecting the adoption of adaptation measures. The Mann-Kendall, Pettitt and Buishand tests and the standardized precipitation index were used to analyze the climate data. Data on adaptation were examined using the chi-square homogeneity test, Kruskal-Wallis test and binary logistic regression. The observed climate trends perfectly corroborated pastoralists' perceptions of significant changes in their local climate since the 1970s: a considerable decrease in annual rainfall and an increase in temperature and frequency of droughts and high winds. There were significant differences (Chi square = 7.603, p = 0.022, df = 2) between small, medium and large pastoralists in the frequency adoption of adaptation strategies, especially between small and large pastoralists (U statistic = 16.000, p = 0.009). The distribution of most adaptation actions also differed significantly between these two groups. Wealthier pastoralists have adopted a greater range of strategies, while poorer pastoralists have less diverse adaptation portfolios, and are more likely to adopt less advantageous strategies such as casual labor. The adoption of adaptation practices was significantly influenced by equipment, educational level, household size, herd size, training received, CC perceptions and agroecological setting. Public interventions to improve the adaptive capacity of pastoralists in Morocco's arid rangelands should be geared towards addressing these determinants and should prioritise small-scale pastoralists. Highlights: Pastoralists' perceptions of climate change accord with observed climate trends. The nature and number of pastoralists' adaptive responses vary by wealth. Poor herders are more likely to adopt problematic strategies such as casual labor. Pastoralists' adaptive responses are specific to local agro-ecological conditions. Perceptions, adaptations and socioeconomics are significantly correlated. Abstract : Climate change, Livestock production, Vulnerability, Adaptation, Determinant, Binary logistic regression.